Assessing the Plain Language Planner for Communication About Common Palliative Care Medications - Wittenberg, Elaine (J Adv Pract Oncol, 2017)
Using plain language to communicate about oncology and palliative care medications and symptoms is recommended as a communication strategy to address patient/family health literacy demands. This study tested the Plain Language Planner©, a provider tool for communicating about medication and symptoms using plain language. Prior to and immediately following an oncology and palliative care nurse educational session, participants (n = 87) role-played about a symptom and medication. Common symptoms (nausea, constipation, and anxiety) and medications were selected. Self-evaluation and peer evaluation addressing the extent of plain language used during the role-play were rated. Plain language characteristics improved post educational role-play sessions for nurses. The largest improvement in plain language was the inclusion of the brand and generic names of medication in relating the drug to the symptom. The pocket guide provided during the educational session was consulted by 86% of nurses during the postsession role-play. Brief training with the Plain Language Planner may improve provider communication and meet patient/family health literacy needs. This resource may be a valuable asset to other health-care disciplines working in oncology and palliative care contexts.